Highly Enantioselective Cross-Electrophile Aryl-Alkenylation of Unactivated Alkenes - Tian, Zhi-Xiong; Qiao, Jin-Bao; Xu, Guang-Li; Pang, Xiaobo; Qi, Liangliang; Ma, Wei-Yuan; Zhao, Zhen-Zhen; Duan, Jicheng; Du, Yun-Fei; Su, Peifeng; Liu, Xue-Yuan; Shu, Xing-Zhong (Journal of the American Chemical Society, 2019)
Enantioselective cross-electrophile reactions remain a challenging subject in metal catalysis, and with respect to data, studies have mainly focused on stereoconvergent reactions of racemic alkyl electrophiles. Here, we report an enantioselective cross-electrophile aryl-alkenylation reaction of unactivated alkenes. This method provides access to a number of biologically important chiral molecules such as dihydrobenzofurans, indolines, and indanes. The incorporated alkenyl group is suitable for further reactions that can lead to an increase in molecular diversity and complexity. The reaction proceeds under mild conditions at room temperature, and an easily accessible chiral pyrox ligand is used to afford products with high enantioselectivity. The synthetic utility of this method is demonstrated by enabling the modification of complex molecules such as peptides, indometacin, and steroids.